A note on normal maximal subgroups in Mal'cev-Neumann division rings - Danh, L.Q.; Deo, T.T. (Carpathian Mathematical Publications, 2024)
The aim of this paper is to describe normal maximal subgroups of the unit groups of Mal'cev-Neumann division rings. As a corollary, we affirmatively answer the conjecture posed in [Akbari S., Mahdavi-Hezavehi M. On the existence of normal maximal subgroups in division rings. J. Pure Appl. Algebra 2002, 171 (2$-$3), 123$-$131] regarding Mal'cev-Neumann division rings of noncyclic free groups.